NEUTROPHILS PERCENTAGE AND AMOUNT OF LEUCOCYTES AFTER CONSUMING RED GUAVA JUICE (Psidium guajava L. Red Cultivar) ON AEROBIC EXERCISE SHORTLY - Yuliana Noor Setiawati Ulvie; Sugiarto - (Universitas Muhammadiyah Semarang, 2014)
Aerobic exercise that is widely proposed to improve health and fitness. Aerobic exercise cancause oxidative stress. The negative impact of oxidative stress that occurred causing inflammation. This event needs to be controlled of antioxidants in the body. The purpose of thisresearch is to study the difference neutrophils percentage and amount of leucocytes between agroup who consumes red guava juice and plain water group on aerobic exercise shortly.The design research is experimental nonrandomized pre-post test control group. The subjectsare students of STPN Yogyakarta who are consumes red guava juice groups and plain water groups. Both groups perform aerobic exercise during 60 minute run. Blood samples formeasuring neutrophils percentage and amount of leucocytes. T-test are used for data analysis.T-test analysis of neutrophils percentage shows that there is difference between red guava juicegroup and plain water group. T-test analysis amount of leucocytes shows that there is nodifference between red guava juice group and plain water group.There is a decrease in the amount of leucocytes but statistically, it is not different. Thepercentage of neutrophils declines and statistically, there is a significant difference between thegroup which consumes red guava juice and the plain water group.Keyword: aerobic exercise shortly, red guava juice, neutrophils percentage, amount of